Macromedia® Coldfusion® MX 7 Web Application Construction Kit - Forta, Ben; Camden, Raymond; Chalnick, Leon; Buraglia, Angela (Adobe Press, 2005)
With more than 75 of the Fortune 100 companies using it (and more than 10,000 organizations employing it worldwide), it's pretty much a given that if you're developing applications for the Web, you're going to need to know ColdFusion at some point! Not to worry: Macromedia ColdFusion MX 7 Web Application Construction Kit provides everything you need to start creating Web-based applications immediately-including the latest version of the ColdFusion Web Application Server and development environment. Author and ColdFusion master Ben Forta starts by covering the fundamentals of Web-based database design and then proceeds to show you how to do everything from create data-driven pages to build complete applications, implement security mechanisms, integrate with e-mail, interact with Macromedia Flash, and more. From design and installation to application deployment and troubleshooting, this guide's got ColdFusion covered, including all the features new to the latest version: structured business reports, rich forms, Enterprise Manager (which lets users cluster multiple ColdFusion servers on a single machine), and more!